Incidence of adverse events and negligence in hospitalized patients: results of the Harvard Medical Practice Study I. Issue 2 (6th April 2004) - Brennan, T A; Leape, L L; Laird, N M; Hebert, L; Localio, A R; Lawthers, A G; Newhouse, J P; Weiler, P C; Hiatt, H H
Abstract : Background: As part of an interdisciplinary study of medical injury and malpractice litigation, we estimated the incidence of adverse events, defined as injuries caused by medical management, and of the subgroup of such injuries that resulted from negligent or substandard care. Methods: We reviewed 30 121 randomly selected records from 51 randomly selected acute care, non-psychiatric hospitals in New York State in 1984. We then developed population estimates of injuries and computed rates according to the age and sex of the patients as well as the specialties of the physicians. Results: Adverse events occurred in 3.7% of the hospitalizations (95% confidence interval 3.2 to 4.2), and 27.6% of the adverse events were due to negligence (95% confidence interval 22.5 to 32.6). Although 70.5% of the adverse events gave rise to disability lasting less than 6 months, 2.6% caused permanently disabling injuries and 13.6% led to death. The percentage of adverse events attributable to negligence increased in the categories of more severe injuries (Wald test χ 2 = 21.04, p<0.0001). Using weighted totals we estimated that among the 2 671 863 patients discharged from New York hospitals in 1984 there were 98 609 adverse events and 27 179 adverse events involving negligence. Rates of adverse events rose with age (p<0.0001). The percentage of adverse events due to negligence was markedly higher among the elderly (p<0.01). There were significant differences in rates of adverse events among categories of clinical specialties (p<0.0001), but no differences in the percentage due to negligence. Conclusions: There is a substantial amount of injury to patients from medical management, and many injuries are the result of substandard care.